LEMBAR KERJA SISWA BERBASIS INKUIRI PADA KURIKULUM 2013 MATERI ASAM BASA - Rusly Hidayah; Alis Rahmawati; Nuril Fatimah; Ni’matul Zahro (Orbital: Jurnal Pendidikan Kimia, 2020)
The obstacles that must be faced in the 2013 Curriculum are the limitations of the media to support the learning process on acid-base material. Research has been conducted with the aim of developing Student Worksheets (LKS) on chemistry subjects based on the 2013 Curriculum which is inquiry based on Acid-Base material for class XI SMA / MA and equivalent. The research was conducted at SMA Al-Hikmah Surabaya using the 4-D development method (Define, Design, Develop, Disseminate). The trial was limited to 19 students of class XI MIA who were randomly selected. This study uses a One Shot Case Study design without a comparison group and a pre-test for the trial phase where students will get a test after students are given treatment using a developed worksheet. The instruments used were study sheets, validation sheets, test sheets and student response questionnaires. Based on the results of the research it is known that this LKS has 76% content feasibility, 90% presentation, 82.5% language, and conformity to the 88% inkuri model based on validation besides that student learning outcomes achieve classical completeness of 94.73% and student responses to student worksheets which is developed tested positive.